2013
DOI: 10.1089/hum.2012.239
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Efficacy and Liver Toxicity Related to Adeno-Associated Virus–Mediated RNA Interference

Abstract: Adeno-associated virus (AAV)-mediated RNA interference shows promise as a therapy for chronic hepatitis B virus (HBV) infection, but its low efficacy and hepatotoxicity pose major challenges. We have generated AAV vectors containing different promoters and a panel of HBV-specific short hairpin RNAs (shRNAs) to investigate factors that contribute to the efficacy and pathogenesis of AAV-mediated RNA interference. HBV transgenic mice injected with high doses of AAV vectors containing the U6 promoter produced abun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 46 publications
1
25
0
Order By: Relevance
“…We suggest that the design of shRNA-based studies should involve careful consideration of several parameters, such as shRNA dose (Grimm, 2011), promoter choice (Lebbink et al, 2011;Sun et al, 2013), AAV serotype (Ehlert et al, 2010) and construct backbone (Boudreau et al, 2009;Han et al, 2011;McBride et al, 2008). These factors should subsequently be tested with respect to titer, construct and specificity in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…We suggest that the design of shRNA-based studies should involve careful consideration of several parameters, such as shRNA dose (Grimm, 2011), promoter choice (Lebbink et al, 2011;Sun et al, 2013), AAV serotype (Ehlert et al, 2010) and construct backbone (Boudreau et al, 2009;Han et al, 2011;McBride et al, 2008). These factors should subsequently be tested with respect to titer, construct and specificity in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…17,18 To further determine whether the protective effect of T 3 is through autophagy, genetic inhibition of hepatic Atg7 via adeno-associated virus serotype 8 (AAV8) vector-delivered shRNA in livers of eu-and hyper-thyroid mice was performed. As expected, knockdown of ATG7 promoted accumulation of SQSTM1 along with suppressed LC3-II production, indicating the inhibition of autophagy in mouse livers (Fig.…”
Section: T 3 Triggers Autophagy To Attenuate Den-induced Hcc Progressionmentioning
confidence: 99%
“…The construction and production of these pseudotyped AAV8 vectors, which contain the H1 promoter and the shRNA coding sequence, has been reported previously. 18 To determine the T 3 effect on DAPK2 expression in vivo, hyperthyroid mice were generated via intraperitoneal injection of T 3 (10 mg/100 g body weight) for 14 d. To induce hypothyroidism in mice, 0.02% methimazole plus 0.1% sodium perchlorate was added to drinking water for 14 d.…”
Section: Animal Model Of Hepatocarcinogenesismentioning
confidence: 99%
“…Expressed shRNAs or pri-miR mimics have the advantage of sustained supply of RNAi activators and are hence more relevant for targeting chronic diseases such as HBV infection. However, several studies reported toxicities that were caused by saturation of the RNAi pathway following overexpression of shRNAs from RNA polymerase (Pol) III promoters [ 85 , 86 , 87 ]. Use of cassettes containing artificial pri-miRs may alleviate this problem as these templates may be expressed from Pol II promoters to afford better transcription control.…”
Section: Manipulation Of Rna Interference (Rnai) To Counter Hbv Inmentioning
confidence: 99%